AN AESTHETIC OF LANGUAGE ON THE PERFORMING ARTS OF RANDAI KUANTAN IN PANGEAN OF KUANTAN SINGINGI AND ITS IMPLICATIONS IN LEARNING AT SCHOOLS - Roza Primadhani, Novi; Elmustian; Zulhafizh (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This article explains the aesthetics of language in the Randai Kuantan performing arts in Pangean District of Kuantan Singingi Regency and its implications in learning at schools. The type of research is qualitative research using descriptive methods. The research was conducted in Pangean District of Kuantan Singingi Regency. The instruments used were searching, obtaining, and collecting data through watching and recording the Randai Kuantan performing art recorded by a recording device. Data collection techniques used are recording techniques, interviews, and transcripts. The data source of the research comes directly from the Randai Kuantan performing art in Pangean District, Kuantan of Singingi Regency. The results of the research indicate that there are five types of diction found in the performing arts of Randai Kuantan, namely: a) denotation, b) connotation, c) abstract, d) concrete, and e) characteristic.